Online Communicative Speaking Tasks to Enhance Students' Speaking Skills - Adhelia, Shafira; Triastuti, Anita (Universitas Islam Negeri Sultan Aji Muhammad Idris Samarinda, 2023)
This study aimed to know whether the use of online communicative speaking tasks can enhance the speaking skills of the ninth graders of a private junior high school in Mungkid, the Province of Central Java, and how well their speaking skills improved. This research was action research that was divided into four stages. Those were reconnaissance, plan, action and observation, and reflection. The research involved 24 students in 9A class of a private junior high school in the academic year of 2022/ 2023. The research was done in two cycles, consisting of eight meetings. The data of the research were collected through quantitative and qualitative data. The quantitative data were from speaking tests and questionnaires. Meanwhile, the qualitative data were obtained from interviews and observation. The quantitative data were analyzed by comparing students' mean scores that were gained from students' speaking performance pre-test and post-test. The qualitative data analysis employed Miles, Huberman & Saldana's (2014) interactive model that consists of data condensation, data display, and drawing and verifying conclusions. The research findings showed that using online communicative speaking tasks effectively enhanced students’ speaking skills and engagement. The result of the post-test showed that there were consistent improvements in students' mean scores in pre-cycle (10.48), cycle I (13.69), and cycle II (18.50). The total improvement from pre-cycle to cycle II was 8.02 points. It indicated that the students had improved in some aspects of speaking skills.